Mechanical deburing and surface finishing technology - Scheider, Alfred F. (Manufacturing engineering and materials processing, 1990)
Focuses on product application principles in the design, development, engineering, and shop floor techniques of deburring, edge contouring, and surface-conditioning methods, systems, and processes highlighting semi-automatic equipment, robotics, and automated machinery.